Application of ChatGPT in Improving Operational Efficiency in the Context of Entrepreneurship - Abu Muna Almaududi Ausat; Andy Rachman; Syamsu Rijal; Suherlan Suherlan; Hizbul Khootimah Azzaakiyyah (Politeknik Ganesha Medan, 2023)
In the ever-evolving digital era, the use of AI has become a major focus in various fields. One example is the application of AI technology in the context of entrepreneurship. Entrepreneurship is an activity that involves developing, launching, and managing new or innovative ventures. In this study, the main objective is to explore the application of ChatGPT in improving operational efficiency in the context of entrepreneurship. The focus of this study is primarily qualitative. Methods for gathering data include paying close attention to detail while viewing and recording data, and then using analytical techniques such as data reduction, visualisation, and inference to draw conclusions. The study results show that the application of ChatGPT in improving operational efficiency in an entrepreneurial context offers a range of significant benefits. In the areas of customer service, marketing and sales, and internal management, ChatGPT can help companies improve customer satisfaction, optimise business processes, save time and resources, and increase productivity and collaboration between teams.